Resíduo úmido de cervejaria em substituição ao alimento volumoso na terminação de cordeiros em confinamento - Frasson, Mônica Feksa (2015)
The objective of this study was to evaluate the effect of increasing levels of substitution of sorghum silage by wet brewers grains (WBG) as forage food on nutrients intake, performance, economic viability, carcass characteristics, components non-carcass and feeding behavior of lambs finished in feedlot. Twenty four non-castrated male lambs, Suffolk breed, single birth were maintained in individual stalls. The treatments consisted of four substitution levels of sorghum silage by RUC (0; 33.5; 66.5 or 100% substitution). It was used roughage and concentrate at 50:50 ratio, based on dry matter. The concentrate was composed of ground corn, soybean meal and mineral mixture. The diets were isoproteic containing 18.81% CP. The animals were slaughtered when they reached the body condition score of 3 (1 to 5 range). Dry matter intakes, organic matter, crude protein, neutral detergent fiber, total carbohydrates, non-fibrous carbohydrates and total digestible nutrients were not influenced by the level of inclusion on WBG in diets. The ether extract intake increased and the acid detergent fiber decreases linearly (P≤0.05) with increasing inclusion level in the diet of WBG. The daily weight gain average increased and feed conversion was lineararly increased (P≤0.05), while in vivo body measurements have not been influenced by the wet brewers grains on the diets. The lamb daily profit (R$/lamb/day) increased linearly (p≤0,05) with elevated WBG content, reflected by reduction in the daily cost with food, from R$ 1,02/lamb/day to R$ 0,58/lamb/day, in the levels 0% and 100% of substitution, respectively. Carcass traits and proportions of commercial cuts were not influenced by replacing sorghum silage by WBG. The proportions of non-carcass components to body weight at slaughter were not affected significantly by substitution sorghum silage per WBG, except diaphragm and omasum (full and empty) that decreased linearly. Concerning ingestive behavior, increased WBG content of diets linearly reduced time expended in feeding, rumination and total chewing, resulting in a linear increase of idle times. The use of WBG for finishing feedlot lambs is an effectively viable alternative and also provides better economic results.